Test signal design for failure detection: A linear programming approach - Rubio Scola, Héctor; Nikoukhah, Ramine; Delebecque, François (Zielona Góra: Uniwersytet Zielonogórski)
A new methodology for the design of filters that permits failure detection and isolation of dynamic systems is presented. Assuming that the normal and the faulty behavior of a process can be modeled by two linear systems subject to inequality bounded perturbations, a method for the on-line implementation of a test signal, guaranteeing failure detection, is proposed.
Keywords: failure detection; large scale programming; failure isolation; bounded perturbations; active detection